2015
DOI: 10.1128/ec.00052-15
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcus Strains with Different Pathogenic Potentials Have Diverse Protein Secretomes

Abstract: bSecreted proteins are the frontline between the host and pathogen. In mammalian hosts, secreted proteins enable invasive infection and can modulate the host immune response. Cryptococcosis, caused by pathogenic Cryptococcus species, begins when inhaled infectious propagules establish to produce pulmonary infection, which, if not resolved, can disseminate to the central nervous system to cause meningoencephalitis. Strains of Cryptococcus species differ in their capacity to cause disease, and the mechanisms und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Recently, Geddes and colleagues identified 61 proteins in the secretions of C . neoformans grown for 16 to 120 hours in minimal media [43], while Campell and coworkers identified 22 secreted proteins after 168 hours growth in RPMI media [29]. In total, 24 of the proteins detected in our study contained predicted secretion signals (SignalP 4.0) [44], 127 were predicted to be non-classically secreted (SecretomeP 2.0) [45], and 17 have been associated with extracellular microvesicles [46].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Geddes and colleagues identified 61 proteins in the secretions of C . neoformans grown for 16 to 120 hours in minimal media [43], while Campell and coworkers identified 22 secreted proteins after 168 hours growth in RPMI media [29]. In total, 24 of the proteins detected in our study contained predicted secretion signals (SignalP 4.0) [44], 127 were predicted to be non-classically secreted (SecretomeP 2.0) [45], and 17 have been associated with extracellular microvesicles [46].…”
Section: Resultsmentioning
confidence: 99%
“…The secretion of these molecules seems to be related to virulence and/or host-pathogen interaction of Paracoccidioides spp. once it has been demonstrated that secretion of immunogenic molecules in other pathogens is implicated in virulence during hostpathogen interaction (Oliveira et al, 2010;Campbell et al, 2015;de Oliveira et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These enzymes are required for many important biological processes, including growth and infection. The importance of the secretome in cryptococcal pathogenesis is apparent from the fact that strain differences in secreted enzymes correlate with their virulence (134). Nonetheless, important questions remain.…”
Section: Resultsmentioning
confidence: 99%